Warlord [videorecording (DVD)] - Brennan, Stuart; Boyd, Billy, 1968-; Gage, Ryan; English, Jennifer (Filmhub, 2025)
Warlord follows a peaceful Wood Elf Warlord, who despises violence, but is forced to take up arms when a cruel Sheriff uses brutal tactics against oppressed citizens. A rebellion grows, and all must choose between death and taxes.